Regularities of films forming on the basis of polyamide-polyvinylpyrrolidone mixtures - Suberlyak, Oleh; Baran, Nataliya; Gnatowski, Adam; Jaruga, Tomash; Melnyk, Yuriy (Publishing House of Lviv Polytechnic National University, 2012)
Modification of polyamide-6 by polyvinylpyrrolidone with molecular mass of 12000±2000 has been carried out using their mixing in formic acid solution followed by solvent evaporation. The possibility of films permolecular structure control, physico-mechnical and thermophysical properties by treatment conditions after their formation has been established. У роботі проведено модифікацію поліаміду-6 полівінілпіролідоном із молекулярною масою 12000±2000 методом змішування їх у мурашинокислому розчині з наступним упарюванням розчинника. Встановлена можливість регулювання надмолекулярної структури, фізико-механічних і теплофізичних властивостей плівок від умов їх обробки після формування.
Закономірності одержання плівкових матеріалів на основі сумішей поліаміду з полівінілпіролідоном
Keywords: polymer; mixture; modification; film; polyamide; polyvinylpyrrolidone; полімери; суміші; модифікація; плівки; поліамід; полівінілпіролідон